Mortality after acute primary mesenteric infarction: a systematic review and meta‐analysis of observational studies. (July 2015) - Adaba, F.; Askari, A.; Dastur, J.; Patel, A.; Gabe, S. M.; Vaizey, C. J.; Faiz, O.; Nightingale, J. M. D.; Warusavitarne, J.
Abstract Aim The primary aim of this study was to determine whether the in‐hospital mortality for acute mesenteric infarction has reduced in the last decade. The secondary aim was to determine if there was a statistical difference in mortality between patients having acute primary mesenteric infarction due to different causes. Method A literature search was performed of PubMed, Ovid (Embase) and Google Scholar databases. Studies on acute mesenteric infarction of primary vascular pathology were included for pooled analyses while studies that had reported comparative mortality between arterial, venous and non‐occlusive mesenteric infarction (NOMI) were included in meta‐analyses. Their quality was assessed using the National Institute for Health and Care Excellence assessment scale. Odds ratios (ORs) of mortality were calculated using a Mantel−Haenszel random effect model. Results The total number of patients was 4527 and the male/female ratio was 1912/2247. The pooled in‐hospital mortality was 63%. There was no significant reduction of in‐hospital mortality rate in the last decade (P = 0.78). There was a significant difference in in‐hospital mortality between acute arterial mesenteric infarction (73.9%) compared with acute venous mesenteric infarction (41.7%) [OR 3.47, confidence interval (CI) 2.43−4.96, P < 0.001] and NOMI (68.5%) compared with acute venous mesenteric infarction (44.2%) (OR 3.2, CI 1.83−5.6, P < 0.001). There was no difference in mortality between acute arterial mesenteric infarction and NOMI (OR 1.08, CI 0.57−2.03, P = 0.82). Conclusion In‐hospital mortality rate has not changed in the last decade. Patients with arterial mesenteric infarction or with NOMI are over three times more likely to die during the first hospital admission compared with those with venous mesenteric infarction.